Extent of Participation of Rural Youth in Farm Operations and Management Activities in Dimapur District of Nagaland - Marina,; S. Borua, (Journal of Agricultural Extension Management, 2020)
Agriculture is an important sector in the economic development and poverty alleviation drive of many countries. Though youth have desirable qualities that can promote agriculture, most of them have strong apathy toward it. This has resulted in mass unemployment and lack of sustainable livelihood among youth. With fewer youth into agriculture, the long term future of agriculture sector is in question. The state of Nagaland predominantly has a rice based agricultural system. The farmers of Nagaland are characterized by small land holding, less cash inflow and poverty. If they cultivate rice crop with proper cultivation methods their cash inflow will be more, which will lead to reduction of rural poverty and increase in capital for further investment.Since majority of the population are youth, they can contribute to a great extent if they participate in farming operations and management. Therefore, a comprehensive study was carried out in Dimapur district of Nagaland in the year 2018 to find out the extent of participation of rural youth in farming operations and management.Purposive and random sampling techniques were used for the selection of respondents. Total 120 respondents were selected for the study. Data were collected by administering a structured schedule. Statistical tools employed to analyse the data included frequency distribution, percentage, mean, standard deviation. The study revealed that majority of the youth had medium level of participation in farming operations and management